Zero-field J-spectroscopy of quadrupolar nuclei - Román Picazo-Frutos; Kirill F. Sheberstov; John W. Blanchard; Erik Van Dyke; Moritz Reh; Tobias Sjoelander; Alexander Pines; Dmitry Budker; Danila A. Barskiy (Nature Communications)
Abstract Zero- to ultralow-field nuclear magnetic resonance (ZULF NMR) allows molecular structure elucidation via measurement of electron-mediated spin-spin J-couplings. This study examines zero-field J-spectra from molecules with quadrupolar nuclei, exemplified by solutions of various isotopologues of ammonium cations. The spectra reveal differences between various isotopologues upon extracting precise J-coupling values from pulse-acquire measurements. A primary isotope effect, $$\triangle J=\left({γ }_{{}^{14}{{{{{\rm{N}}}}}}}/{γ }_{{}^{15}{{{{{\rm{N}}}}}}}\right)J_{{}^{15}{{{{{\rm{N}}}}}}{{{{{\rm{H}}}}}}}-J_{{}^{14}{{{{{\rm{N}}}}}}{{{{{\rm{H}}}}}}}≈ -58$$ △ J = γ 14 N / γ 15 N J 15 N H − J 14 N H ≈ − 58 mHz, is deduced by analysis of the proton-nitrogen J-coupling ratios. This study points toward further experiments with symmetric cations containing quadrupolar nuclei, promising applications in biomedicine, energy storage, and benchmarking quantum chemistry calculations.